2021
DOI: 10.3390/molecules26082127
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides to One Story—Aroma Chemical and Sensory Signature of Lugana and Verdicchio Wines

Abstract: Lugana and Verdicchio are two Italian white wines with a Protected Designation of Origin (PDO) label. These two wine types are produced in different regions using the same grape variety. The aim of this work is to investigate the existence of volatile chemical markers that could help to elucidate differences between Lugana and Verdicchio wines both at chemical and sensory levels. Thirteen commercial wine samples were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS), and 76 volatile compounds were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Other important benzenoids: methyl salicylate is an organic ester naturally produced by many plants, particularly wintergreens, and also present in wine, sometimes in quite high quantities, such as in the Verdicchio and Lugana varieties [38,39]. It was demonstrated that it could be present in both free and bound form (MeSA glycosides).…”
Section: Gewürztraminer Winementioning
confidence: 99%
“…Other important benzenoids: methyl salicylate is an organic ester naturally produced by many plants, particularly wintergreens, and also present in wine, sometimes in quite high quantities, such as in the Verdicchio and Lugana varieties [38,39]. It was demonstrated that it could be present in both free and bound form (MeSA glycosides).…”
Section: Gewürztraminer Winementioning
confidence: 99%
“…Simultaneously, control samples were stored at 4 °C. All samples were prepared in triplicate and analyzed by headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography−mass spectrometry (GC−MS) following the method of Slaghenaufi et al 32 Influence of pH on DMS Formation during Aging. An Amarone wine from vintage 2015 (initial concentration of DMS: 10.3 μg/L and pH 3.45) was spiked with S-methylmethionine (SMM) in the form of DL-methionine methylsulfonium chloride (Merck, Darmstadt, Germany) at 6.4 mg/L, in order to have a final concentration of 2 mg/L of DMS equivalents.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Simultaneously, control samples were stored at 4 °C. All samples were prepared in triplicate and analyzed by headspace solid-phase microextraction (HS-SPME) coupled to gas chromatography–mass spectrometry (GC–MS) following the method of Slaghenaufi et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile sulfur-containing compounds were quantified according to [32] by placing 10 mL of sample with 100 µL of internal standard (DMS-d6, 2 mg/L in ethanol) and 3 g of NaCl into a 20-mL glass vial. SPME extraction was performed using a polydimethylsiloxanedivinylbenzene fibre (PDMS/DVB) (Supelco, Bellafonte, PA, USA) exposed to sample headspace for 30 min.…”
Section: Analysis Of Volatile Compoundsmentioning
confidence: 99%